2016
DOI: 10.1016/j.medici.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum cytokines in acute appendicitis and acute mesenteric lymphadenitis among children

Abstract: Serum IL-6 with a cut-off value of 4.3pg/mL and WBC with a cut-off value of 10.7×10/μL assessed together will yield more sensitivity for AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…In a study performed for AA and AML differential diagnosis, the monocyte chemoattractant protein-1 (MCP 1) ratio was found not to be different between these two groups. In this study, although the MCP 1 ratio was high in AA, there was no statistically significant difference between the two groups [11]. This result was compatible with our work regarding the M percentage in the discrimination of both groups (p = 0.15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study performed for AA and AML differential diagnosis, the monocyte chemoattractant protein-1 (MCP 1) ratio was found not to be different between these two groups. In this study, although the MCP 1 ratio was high in AA, there was no statistically significant difference between the two groups [11]. This result was compatible with our work regarding the M percentage in the discrimination of both groups (p = 0.15).…”
Section: Discussionsupporting
confidence: 92%
“…When looking at the literature, there was generally no significant difference in age (range: 9-13) or gender in studies comparing AML and AA patients [8,11]. Conversely, there was a study that found significant differences in age between AA and AML patients (male vs. female: 10.3 vs. 7.9 years) [7].…”
Section: Discussionmentioning
confidence: 99%
“…As IL-6 has been reported to induce the acute phase response caused by bacterial endotoxemia. Zviedre et al reported that IL-6 can provide more sensitivity in acute appendicitis when used in parallel with a white blood count (WBC) to improve the sensitivity of a diagnosis of appendicitis [ 13 ]. However, PTX3 has been linked to various cytokines as an inflammatory response related to IL-6.…”
Section: Reviewmentioning
confidence: 99%
“…Laboratory data show that serum levels of the white blood cell (WBC), C-reactive protein (CRP), and interleukin-6 are related to AA[ 44 - 46 ]. The most reliable marker is neither the neutrophil count nor CRP, but the WBC count[ 1 , 44 ].…”
Section: Diagnostic Valuementioning
confidence: 99%
“…The WBC count and CT findings equally provide surgeons with complementary information in discerning the necessity for an urgent operation[ 36 , 44 , 47 ]. With development of WBC measurement and enhanced CT imaging, the rate of negative appendectomy has decreased to as low as < 5%[ 1 , 36 , 40 , 48 ].…”
Section: Diagnostic Valuementioning
confidence: 99%